Pengaruh Pengetahuan Investasi, Kemudahan Penggunaan dan Risiko Investasi Terhadap Minat Berinvestasi Online : Studi Kasus Generasi Milenial - Lestarinah Silalahi; Fathihani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This research purposes to determine the factors which contribute to the millennial generation's interest in investing. This research uses a quantitative method by using survey data and using a survey form as a data collection tool. Data analysis in this research uses the partial least squares program to determine the effect or lack of correlation between latent variables. Based on data analysis, the results of this research indicate that the indicators in this research are valid and reliable. Investment knowledge has a significant positive effect on millennials' interest in investing, ease of use has a significant positive effect on millennials' interest in investing, and investment risk has no significant effect with a negative effect on millennials' interest in investing